Ihor Stasyuk’s 75th birthday (Condensed Matter Physics, 2013)
Quantum many body physics and solid state theory in Lviv and Ukraine have always been linked with the name of Professor Ihor Stasyuk, a prominent scientist who celebrates his 75th birthday.